COMPARATIVE STUDY OF LEVELS OF SELECTIVE OXIDATIVE STRESS MARKERS (MALONDIALDEHYDE, ZINC, AND ANTIOXIDANT VITAMINS A, E, AND C) IN ISCHEMIC AND NON-ISCHEMIC HEART DISEASE PATIENTS SUFFERING FROM TYPE- 2 DIABETES - A Altoum, Abd Elgadir; Osman, Ahmed L; Babker, Asaad Ma (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the current study is to compare the levels of oxidative stress markers malondialdehyde (MDA), zinc, and antioxidant Vitamins (A, E, and C) in ischemic heart disease (IHD) and non-IHD patients with diabetes mellitus. Method: This is cross-sectional study group, conducted in the advanced diagnostic center (Khartoum- Sudan) from the period May 2013 to August 2015. Comprised 100 healthy subjects were, control group with mean (fasting blood sugar) 5.61=m mol/L, the age ranged from 22 to 78 years old, the average of the age was 50.1 years. 300 patients (78 IHD and 222 without) as cases groups, the ages ranged from 30 to 80 years. The age average was 51.2 years, all samples were in a state of fasting for 12 h, and the data were collected using a structured questionnaire and direct interview to collect information. Blood specimens were collected from both groups, and plasma levels of MDA, zinc, and antioxidant Vitamins (A, E, and C) were determined. Results: There was a significant difference between the level of serum Vitamin A, E, and MDA in diabetic patients with IHD and those diabetic without IHD (p<0.05). No significant differences in serum Vitamin C level between both groups (p>0.05). Conclusion: Due to the significant differences in serum Vitamin A, E, Zinc, and MDA between diabetics with IHD and diabetics without IHD, these parameters can be used as prognostic markers for prediction of oxidative stress and antioxidant stress of diabetic patients with IHD complications.